Neurocognitive evaluation in patients with intracranial Meningiomas: A systematic review - Christina K. Arvaniti; Alexandros G. Brotis; Maria E. Karaferi; Antonios D. Benos; Kerasia Goupou; Kostas N. Fountas (Brain and Spine)
Introduction: Meningiomas remain the most frequently occurring intracranial, extra-axial, space-occupying lesions. Aspects such as neurocognitive function and quality of life become more and more crucial. Several meningioma patients present with evidence of neurocognitive impairment, behavioral disorders, or even psychiatric symptoms. Research question: This review synthesizes the current literature on neurocognitive evaluation in intracranial meningioma patients, focusing on the range of cognitive domains affected (Q1), the assessment tools utilized (Q2), and the relationship between tumor characteristics and cognitive outcomes (Q3). Materials and methods: A PRISMA-compliant systematic review was performed. We searched PubMed, Scopus, and Dimensions, to identify relevant studies published to date. Additionally, we examined the reference lists of the selected studies. The most recent literature search was conducted on January 31, 2025. Results: We included 30 studies. The neurocognitive domains examined encompass a range of functions, such as executive functioning, memory, attention, perceptual speed, visuospatial abilities, verbal fluency, cognitive flexibility, and cognitive function. The most frequently used tests as demonstrated in current literature are WAIS, RAVLT, WMS, TMT, Stroop test and CNS Vital signs. Tumor size, increased age, peritumoral edema and skull base meningiomas were all associated with worse performance in various cognitive domains. Discussion and conclusion: Our analysis reveals that meningiomas can significantly impact cognitive function, affecting various domains such as memory, executive function, attention, and language. Most of these domains seem to improve postoperatively. A common battery test for neurocognitive evaluation in all meningioma patients would provide us with more comparable and reliable results.